NATURAL AND ANTHROPOGENIC CHANGES IN MOUNTAIN FOREST ECOSYSTEMS OF UKRAINIAN CARPATHIANS AND THE WAYS FOR MAINTANING THEIR STABILITY - Parpan, T. V.; Hudyma, V. D. (Forestry and Forest Melioration, 2018)
Introduction The aim and practical objective of this work is to analyze the extent of natural and anthropogenic changes (successions) in mountain forest ecosystems of the Ukrainian Carpathians, which took place over the last two or three centuries as the basis for assessing stability and sustainability of mountain forests, as well as predictive planning strategy of the modern multipurpose forest management. Materials and methods To analyze the extent of natural and anthropogenic changes in forest mountain ecosystems, the relational database for each forest unit was used to determine the accordance of actual stand composition to the respective forest type. Out of several succession forms, the following types were analyzed: the exogenous local anthropogenic successions by V. M. Sukachev or ecodynamic (allogeneic) successions, local natural and anthropogenic successions by B. M. Mirkin and L. G. Naumova or natural and anthropogenic successions by P. D. Yaroshenko. Results and discussion Over the past two or three centuries, extensive succession processes have taken place in the mountain conditions of the Carpathians as a result of anthropogenic impact (mainly clear main cuttings and clear sanitary cuttings), which reduced the stability of mountain ecosystems. In the process of phylogeny, 11 formations of forests have formed in the mountains of the Ukrainian Carpathians. The formations of the European spruce, silver fir and beech are the most extensive in size and stock. In the current forest cover, the area of mountain forests of all formations, which are subordinated to the State Agency of forest resources of Ukraine, is 1022 thousand hectares. In the primary forest cover, the formation of spruce forests occupied an area of 370 thousand hectares, belonging to nine types of site conditions. It formed five sub-formations and 19 forest types. The age structure of the modern spruce dendrocoenosis is uneven due to the use of clear cuttings. The area of formations of fir forests in the primary forest cover was around 190 thousand hectares and covered six types of site conditions. Changing of the ecosystem edifier in these forests is the most extensive and covers an area of around 95 thousand hectares. The derivative spruce stands occupy around 55 thousand hectares in the modern cover. Modern mountain fir forests are the most anthropogenically-altered and require comprehensive environmental measures. The formation of mountain beech forests has the largest area, 431.0 thousand hectares. Its main area (73 %) is on the south-western Transcarpathian megaslope. Seven types of site conditions, nine sub-formations and 29 forest types have formed within this formation. The age structure of all mountain forests of the Ukrainian Carpathians is radically changed. In the current forest cover, distribution of stands by age groups is extremely uneven: young stands of the first age group account for 7.5 %, young stands of the second age group account for 10.1%, middle-aged stands account for 48.1 %, almost mature stands account for 13.7 %, mature stands account for 14.5 %, and overmature stands account for 6.1 %, indicating extensive clear-cutting in the 50s of last century. Conclusions Mountain forests of the Ukrainian Carpathians were drastically changed by the indexes of phytocoenotic structure – change of the composition of dominant species and age structure. The most extensive changes occurred in the formation of fir forests. The methodological foundation for the assessment of natural and anthropogenic changes is based on the forestry and ecological classification by P. S. Pogrebnyak and D. V. Vorobyov with refinements and additions by M. A. Holubets. Natural and anthropogenic successions affected the stability of forest ecosystems. The ways to support them are possible only by the conversion to the close-to-nature forestry. Acknowledgments The paper prepared within the framework of the international project “HYDROFOR: Systems of optimal forest management for enhancing the hydrological role of forests in preventing the floods in Bodrog river catchment” (HUSKROUA/1101/262).